PENGARUH BUKU SAKU GIZI TERHADAP TINGKAT PENGETAHUAN GIZI PADA ANAK KELAS 5 MUHAMMADIYAH DADAPAN DESA WONOKERTO KECAMATAN TURI KABUPATEN SLEMAN YOGYAKARTA - Eliana, Desy; Solikhah, Solikhah (Kes Mas: Jurnal Fakultas Kesehatan Masyarakat, 2012)
Background :Nutrition education is very important given since entering primary school for chil-dren have good nutrition knowledge level. The level of nutrition knowledge a person will influ-ence the attitudes and behavior in selecting foods that will ultimately affect the nutritional state of the individual concerned. Nutrition pocket book is one of the methods of health education in the form of print media that can provide information about nutrition and to increase nutrition knowledge in children, with increased knowledge of nutrition is expected to prevent diseases caused by malnutrition. This study aims to determine the effect of nutrition on the pocket book on child nutrition knowledge level of grade 5 elementary school Muhammadiyah Dadapan Vil-lage District Wonokerto Turi Sleman Yogyakarta Method: Type of research is quasi Exsperiment with pre test and post test one group design. The samples were grade 5 students Muhammadiyah Dadapan Village Elementary School Dis-trict Wonokerto Turi Sleman Yogyakarta, which numbered 30 students, using primary data. Measurement of knowledge conducted using questionnaires before and after the pocket book. Data analysis using Paired Sample T-Test Results: There is increased knowledge about nutrition in children 5th grade elementary school Muhammadiyah Dadapan Village District Wonokerto Turi Sleman Yogyakarta with an average value, it is known that the mean value before it is given a pocket book and the mean is given after each pocket book for 71.33 and 91.07. Mean shows the average difference before and after the administration of a paperback book. Significant value Sig (2-tailed) (0.000) <0025 and 95% Confidence interval -22.820 <1> -16.646 (does not include item 1). The probability or pos-sibility of true hypotheses is small so Ho is rejected, it states that there is a difference of mean between before and after given a pocket book, pocket book on nutrition so that gives the effect of nutrition knowledge of elementary school children grades 5 Muhammadiyah Dadapan Wonokerto In the village of Turi Sleman District, Yogyakarta. Conclusion: The Pocket Book of Nutrition have a significant influence on the increased knowl-edge of nutrition in children 5th grade elementary school Muhammadiyah Village Dadapan Wonokerto Turi Sleman District, Yogyakarta. Keywords: pocket book of nutrition, Nutrition Knowledge Levels, Nutrition in Children